2010
DOI: 10.1111/j.1365-2966.2009.15772.x
|View full text |Cite
|
Sign up to set email alerts
|

Super asymptotic giant branch stars. I - Evolution code comparison

Abstract: We present an extensive set of detailed stellar models in the mass range 7.7–10.5 M⊙ over the metallicity range Z= 10−5–0.02. These models were produced using the Monash University version of the Mount Stromlo Stellar Structure Program (monstar) and follow the evolution from the pre‐main sequence to the first thermal pulse of these super asymptotic giant branch stars. A quantitative comparison is made to the study of Siess. Prior to this study, only qualitative comparisons and code validations existed in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 34 publications
8
95
0
Order By: Relevance
“…By a simple integration of the Kroupa, Tout & Gilmore (1993) mass function this implies that one SAGB progenitor should form per 453 M⊙ of total star formation. The SAGB stage lasts for a few 10 5 yr while the total lifetimes of the progenitors are a few 10 8 yr (Doherty et al 2010(Doherty et al , 2014. Hence roughly one out of every thousand stars of the correct mass should be a SAGB star at any given time.…”
Section: Probabilitiesmentioning
confidence: 99%
“…By a simple integration of the Kroupa, Tout & Gilmore (1993) mass function this implies that one SAGB progenitor should form per 453 M⊙ of total star formation. The SAGB stage lasts for a few 10 5 yr while the total lifetimes of the progenitors are a few 10 8 yr (Doherty et al 2010(Doherty et al , 2014. Hence roughly one out of every thousand stars of the correct mass should be a SAGB star at any given time.…”
Section: Probabilitiesmentioning
confidence: 99%
“…) we know that the stellar evolution code STAREVOL (Siess 2010), presents the same convergence problems during late massive AGB and super-AGB evolution. Both codes and their respective super-AGB models have been described by Doherty et al (2010). It is worth noting that such convergence problems are common.…”
Section: Physical Description Of the Instabilitymentioning
confidence: 99%
“…Recent analysis (Denissenkov et al 2013) has shown that such a stratified chemical structure of the core might occur because of the effect of convective boundary mixing, which is able to prevent the C-burning flame from reaching the central regions of the star. In fact, similar structures that are composed of a central carbon-rich region surrounded by an ONe (i.e., carbon-poor) zone have been found using different evolutionary codes, such as MONSTAR (Doherty et al 2010) or the code used by Garcia-Berro & Iben (1994). The question is nevertheless far from closed (see, e.g., Waldman & Barkat 2007), and it is interesting to analyze the outcome of different configurations of such CONe cores.…”
Section: Introductionmentioning
confidence: 89%
“…They are the result of carbon burning starting very far off-center in IMS with core masses of ∼1.04-1.06 M , and switching off before reaching the center because of cooling by neutrinos at the innermost region of the core. In the cases that concern us, i.e., the lightest objects able to ignite carbon, suitable conditions for carbon burning are not recovered after the first off-center burning episode (for instance, Ritossa et al 1999;Gil-Pons & García-Berro 2001;Siess 2006;Doherty et al 2010). …”
Section: Formation Of Hybrid Cone Wdsmentioning
confidence: 99%
See 1 more Smart Citation